Peran Sinergis Antara Zakat Dan Pajak Sebagai Instrumen Utama Dalam Mewujudkan Kesejahteraan Masyarakat Di Indonesia - Ahsin Haris Ulinnuha (CV. ITTC INDONESIA, 2025)
Social welfare is one of the main objectives of Indonesia's national development, as stated in the Preamble of the 1945 Constitution, which aims to “establish social justice for all the people of Indonesia.” To realize this national ideal, the state requires effective and sustainable financial instruments. Two instruments that hold great potential in promoting social welfare are taxation and zakat. Tax is a compulsory obligation for every citizen to the government, the proceeds of which are used to finance various public needs, ranging from infrastructure and education to social security. Taxes are universal, binding, and formally regulated by law. On the other hand, zakat is a religious obligation for Muslims, functioning as a tool for the redistribution of wealth. Zakat carries a strong social character and is oriented toward justice and compassion, particularly for the vulnerable segments of society. As the country with the largest Muslim population in the world, Indonesia has an enormous potential for zakat collection. According to data from the National Board of Zakat (BAZNAS), the national zakat potential is estimated to exceed IDR 300 trillion per year. However, the actual collection falls significantly short of this potential. At the same time, state tax revenues also face ongoing challenges, such as suboptimal compliance rates and potential fiscal leakages.